1999
DOI: 10.1074/jbc.274.23.16040
|View full text |Cite
|
Sign up to set email alerts
|

Yap1 and Skn7 Control Two Specialized Oxidative Stress Response Regulons in Yeast

Abstract: Aerobic organisms have to maintain a reduced cellular redox environment in the face of the prooxidative conditions of aerobic life. The incomplete reduction of oxygen to water during respiration leads to the formation of redox-active oxygen intermediates such as the superoxide anion radical (O 2 . ), hydrogen peroxide (H 2 O 2 ), and the hydroxyl radical (for review see Refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
525
5
11

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 518 publications
(579 citation statements)
references
References 55 publications
31
525
5
11
Order By: Relevance
“…Other regulators of oxidative stress, many of which act as Yap1p co-regulators, include Skn7p (Lee et al, 1999), Sko1p (Rep et al, 2001), Hsf1p (Trott and Morano, 2003) and Yap2p (our unpublished results), itself a member of the YAP family.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Other regulators of oxidative stress, many of which act as Yap1p co-regulators, include Skn7p (Lee et al, 1999), Sko1p (Rep et al, 2001), Hsf1p (Trott and Morano, 2003) and Yap2p (our unpublished results), itself a member of the YAP family.…”
Section: Introductionmentioning
confidence: 77%
“…This response, mediated by the two zinc finger transcription factors, Msn2p and Msn4p, acts via a consensus cis-regulatory element termed the stress response element (STRE-C 4 T) present on target gene promoters. Previous studies have demonstrated that a significant number of genes induced by oxidative stress shows Msn2/4p-dependence (Gasch et al, 2000;Lee et al, 1999), pointing towards an overlap between this and the Yap1p regulon (Hasan et al, 2002). Similarly, such co-regulation has also been described between Msn2/4p and Hsf1p under various conditions of cellular stress (Amoros et al, 2001).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The Yap1 protein has previously also been shown to be important in controlling both resistance and gene regulation in response to cadmium (Stephen and Jamieson, 1997;Stephen et al, 1995;Wemmie et al, 1994;Wu and Moye-Rowley, 1994), though the mechanism by which the Yap1 protein regulates the H 2 O 2 , cadmium and mercury regulation of gene expression is clearly complex (Lee et al, 1999). The fact that an adaptive response to mercury is still partially inducible in a yap1 mutant would also seem to point to the existence of additional regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In Saccharomyces cerevisiae surprisingly little is known about the mechanism of mercury resistance, whereas a considerable amount is known about resistance mechanisms towards copper and, to a lesser extent, cadmium (Gross et al, 2000;Lee et al, 1999;Vido et al, 2001). The mechanism of mercury toxicity is thought to involve the direct binding of mercury to thiol-containing compounds, such as glutathione, thereby resulting in oxidative stress.…”
Section: Introductionmentioning
confidence: 99%